2020
DOI: 10.1016/j.heliyon.2020.e03268
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant, antibacterial, in vivo immunomodulatory, antitumor and hematological potential of exopolysaccharide produced by wild type and mutant Lactobacillus delbureckii subsp. bulgaricus

Abstract: Biological evaluation of exopolysaccharides (EPS) produced by wild type and mutant Lactobacillus delbureckii (EPSWLD and EPSMLD) was investigated. Varying degrees of functional groups associated with polysaccharides were present thus confirming the EPS. The EPSs had strong antioxidant potential in a dose dependent (0.5-10 mg/ mL) manner. EPSWLD and EPSMLD exhibited the highest 1,1-diphemy 1-2-picryl-hydrazyl (DPPH) activity (73.4 % and 65.6 %), total antioxidant activity (1.80 % and 1.42 %), H 2 O 2 scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 53 publications
2
25
0
1
Order By: Relevance
“…EPS from Lactobacillus plantarum NCU116 increased the expression of pro-apoptotic genes such as Fas, FasL and c-Jun, through toll-like receptor-2 (TLR-2) which mediates apoptosis in mouse intestinal epithelial cancer cells [108]. EPS produced by wild and mutant Lactobacillus delbrueckii has been studied to disclose their inhibitory role on tumor cell by the reduction in carcino-embryonic antigen level of tumor induced mice [109]. Silver nanoparticles synthesized using EPS from Lactobacillus brevis demonstrates various applications in the biomedical field especially as a powerful anti-proliferative agents against various human cancer cell lines [110].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…EPS from Lactobacillus plantarum NCU116 increased the expression of pro-apoptotic genes such as Fas, FasL and c-Jun, through toll-like receptor-2 (TLR-2) which mediates apoptosis in mouse intestinal epithelial cancer cells [108]. EPS produced by wild and mutant Lactobacillus delbrueckii has been studied to disclose their inhibitory role on tumor cell by the reduction in carcino-embryonic antigen level of tumor induced mice [109]. Silver nanoparticles synthesized using EPS from Lactobacillus brevis demonstrates various applications in the biomedical field especially as a powerful anti-proliferative agents against various human cancer cell lines [110].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…strains yielded amounts of EPS ranging from 380 to 737.3 mg/L. In the studies by Adebayo-Tayo et al (2018) [117] and Adebayo-Tayo et al (2020) [118], the EPS production yields were compared between mutant and wild LAB strains, where the wild strain of Lactobacillus delbrueckii has been shown to be more effective (5.57 g/L). Nonetheless, in the same study [117] the EPS yields of 5.49 and 5.58 g/L with a wild and mutant strain of Weissella confusa were obtained.…”
Section: Capacity Of Presumptive Lactic Acid Bacteria To Produce Exopmentioning
confidence: 99%
“…Several other authors also reported the impact of culture medium composition on the level of EPS produced by LAB [ 34 , 37 , 42 , 55 , 57 ]. In this regard, a number of media specifically developed for EPS production, including skim or partially skim milk, whey based medium, semi-defined medium, chemically defined medium and basal minimum medium have also been applied [ 58 ].…”
Section: Eps-producing Lactic Acid Bacteriamentioning
confidence: 99%
“…bulgaricus showed a high amount of EPS production ca. (5.5 g/L) in modified skim milk with glucose as a carbon source [ 42 ]. Additionally, S. thermophilus has been found to exhibit high EPS production in milk medium in comparison to MRS or M17 broths [ 59 ].…”
Section: Eps-producing Lactic Acid Bacteriamentioning
confidence: 99%